Pengaruh Kegiatan Bermain Peran dalam Mengembangkan Kecerdasan Linguistik Anak Usia Dini - Fathia, Wilda; Yuningsih, Restu; Indriyani, Vivi; Fitri, Hani Melda Asrul (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Linguistic intelligence is one aspect that must be stimulated and utilized appropriately from an early age. Because young children often imitate what they hear and see. However, not all children are optimal in developing their linguistic intelligence. Several things related to linguistic intelligence include being able to convey what is thought through verbal means in the form of words. Therefore, children's learning processes need to be modified by applying role-playing learning methods. This research aims to prove the application of role playing in improving children's linguistic intelligence. This type of research is an experiment with a one group pretest and posttest design. The data for this research are scores from observations of children's linguistic intelligence. The research results show that the application of role playing methods in learning is proven to be able to improve and develop the linguistic intelligence of young children.